Implementation matters: program impact pathway analysis of four sectoral nutrition-sensitive interventions in Anambra and Kebbi states, Nigeria - Oluchi Ezekannagha; Scott Drimie; Dieter Von Fintel; Busie Maziya-Dixon; Xikombiso Mbhenyane (Global Health Action, 2025)
Background Undernutrition in early childhood can be reduced when large-scale, nutrition-sensitive programs are delivered with adequate dose, reach, fidelity, and recruitment. Objectives This study (i) investigates the implementation and impact pathways of four nutrition-sensitive programs in Kebbi and Anambra states, Nigeria: Early Childhood Development Education (ECCDE), Environmental Sanitation, Skills Acquisition, and Agricultural Transformation Support Program (ATASP-1) and (ii) identifies cross-sector factors that enable or hinder effective dose, reach, fidelity, and recruitment. Methods The study employs qualitative methods such as document reviews, in-depth interviews, and site observations to explore the complexity of program delivery and the contextual factors that influence its outcomes. Results All four programs showed dose–reach–fidelity–recruitment gaps in varying degrees: irregular training and equipment delayed dose; rural and low-income communities were least reached; weak quality control cut fidelity; and recruitment seldom penetrated remote areas. Barriers across sectors included insufficient infrastructure, shortages of trained personnel, and bureaucratic funding delays. Programs with robust community engagement, active multi-stakeholder collaboration, timely resource flow, and short ‘reviewandadapt’ cycles (ATASP1 in both states; ECCDE in Anambra) overcame many shortfalls, whereas those lacking these features underperformed (Environmental Sanitation in Anambra; Skills Acquisition in Kebbi). Conclusion Closing Nigeria’s nutrition-sensitive implementation gap demands a dual response: fix tangible barriers – staffing, infrastructure, and procurement – and institutionalize community-led planning and adaptive management to keep dose–reach–fidelity–recruitment on track. Doing so will improve program reach and quality and accelerate progress against child undernutrition.